Association of clot burden score with radiographic and clinical outcomes following Solitaire stent retriever thrombectomy: analysis of the SWIFT PRIME trial. (15th September 2016) - Mokin, Maxim; Levy, Elad I; Siddiqui, Adnan H; Goyal, Mayank; Nogueira, Raul G; Yavagal, Dileep R; M Pereira, Vitor; Saver, Jeffrey L
Abstract : Background: The clot burden score (CBS) was developed as a tool to evaluate the extent of intracranial thrombus burden in patients with anterior circulation acute ischemic stroke. CBS is based on the presence or absence of contrast opacification on CT angiography (CTA). Its value in predicting radiographic and clinical outcomes in patients given endovascular stroke therapy remains unknown. Objective: To evaluate the relationship between CBS and outcomes after stent retriever thrombectomy in the interventional arm of the SWIFT PRIME trial. Methods: CBS was calculated for the endovascular arm (IV tissue plasminogen activator plus Solitaire stent retriever) of SWIFT PRIME using baseline CTA. The cohort of 69 patients was divided into three groups according to their CBS values: CBS 0–5 (n=14), CBS 6–7 (n=23), and CBS 8–9 (n=32). Results: The mean age of the 69 patients who formed the study cohort was 63.2±13.1 years, mean National Institutes of Health Stroke Scale score was 16.8±4.5, and 55% of the patients were male. There was no difference in clinical characteristics among the three groups, except for the baseline Alberta Stroke Program Early CT Score (p=0.049). The site of proximal occlusion varied significantly among the three groups (p<0.001). Rates of successful recanalization (TICI 2b/3), complete recanalization (TICI 3 only) and of good clinical outcome at 3 months were similar among the three groups (p=0.24, p=0.35, and p=0.52, respectively). Conclusions: The combination of IV thrombolysis and stent retriever thrombectomy with the Solitaire device is highly effective in achieving successful recanalization and a good clinical outcome throughout the entire range of CBS values.